Infection of pigs with African swine fever virus via ingestion of stable flies (Stomoxys calcitrans). Issue 5 (7th June 2018) - Olesen, Ann Sofie; Lohse, Louise; Hansen, Mette Frimodt; Boklund, Anette; Halasa, Tariq; Belsham, Graham J.; Rasmussen, Thomas Bruun; Bøtner, Anette; Bødker, René
Abstract: Within Eastern Europe, African swine fever virus (ASFV) has unexpectedly spread to farms with high biosecurity. In an attempt to explain this process, pigs were allowed to ingest flies that had fed on ASFV‐spiked blood, which had a realistic titre for an infected pig. Some of the pigs became infected with the virus. Thus, ingestion of blood‐sucking flies, having fed on ASFV‐infected wild boar before entering stables, represents a potential route for disease transmission.